Mass distribution of the 237Np photofission fragments at energy 12.5 MeV - O. O. Parlag; V. T. Maslyuk; A. I. Lengyel; Yu. V. Kibkalo (Ядерна фізика та енергетика)
Semiconductor gamma-spectroscopy method has been used for measuring the cumulative yields of the 28 fragments of 237Np photofission for 21 mass chains at 12.5 MeV bremsstrahlung maximum energy. Resulted mass distribution of heavy fragments shows the higher yields in the mass region 133 - 134, 138 - 140 and 145 - 146.